Conspicuous Work: Peer Working Time, Labour Supply and Happiness for Male Workers - Marion Collewet; Andries de Grip; Jaap de Koning (Institute for the Study of Labor (IZA), 2015)
This paper uncovers 'conspicuous work' as a new form of status seeking that can explain social interactions in labour supply. We analyse how peer working time relates to both labour supply and happiness for Dutch male workers. Using a unique measure of peer weekly working time, we find that men's working time increases with that of their peers and that peer working time is negatively related to men's happiness. These findings are consistent with a 'conspicuous work' model, in which individuals derive status from working time.
Keywords: J22; I31; D62; 330; well-being; social norms; working hours